"It looks good on paper, but It was never meant to be real": mixed-gender events in the Paralympic Movement - Dean, N. A.; Bundon, A.; Howe, P. D.; Abele, N. (Adapted Physical Activity Quarterly, 2024)
Although the Paralympic Games have been around for over 60 years, women remain underrepresented in almost all aspects of the Paralympic Movement. It has been suggested that a way to increase women`s involvement is through the implementation of mixed-gender events. On paper, this approach makes sense. However, when it comes to the implementation of mixed-gender opportunities for women, it is less clear how effective these events are in increasing participation by women in Para sport. Through document analysis and interviews with athletes and organizers of mixed-gender Paralympic sport, we explore the various strategies that four mixed-gender sports have used to address the issue of gender parity. Using critical feminist theories, we illustrate how larger social, political, and cultural ideas about gender influence women`s experiences within these events and discuss the potential of using mixed-gender initiatives to address gender parity within the Paralympic Movement.